3rd IEEE International Symposium on Biomedical Imaging: Macro to Nano, 2006.
DOI: 10.1109/isbi.2006.1625101
|View full text |Cite
|
Sign up to set email alerts
|

Joint Detection-Estimation of Brain Activity in fMRI using an Autoregressive Noise Model

Abstract: Different approaches have been considered so far to cope with the temporal correlation of fMRI data for brain activity detection. However, it has been reported that modeling this serial correlation has little influence on the estimate of the hemodynamic response function (HRF). In this paper, we examine this issue when performing a joint detectionestimation of brain activity in a given homogeneous region of interest (ROI). Following [1], we adopt a space-varying AR(1) temporal noise model and assess its influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…In short, it has been shown that the gamma-Gaussian mixture model (GaGMM) introduced on the NRLs is more efficient than a two-class Gaussian mixture model (GMM) in terms of specificity: it provides a better control of the false positive rate. Similar conclusions have been drawn in (Makni et al, 2006b) when considering an AR(1) noise model instead of a white Gaussian one in combination with a GMM prior. As the two changes induce higher computation time, it is worth assessing which modelling effort is preferable i.e.…”
Section: Results On Synthetic Datasupporting
confidence: 84%
See 3 more Smart Citations
“…In short, it has been shown that the gamma-Gaussian mixture model (GaGMM) introduced on the NRLs is more efficient than a two-class Gaussian mixture model (GMM) in terms of specificity: it provides a better control of the false positive rate. Similar conclusions have been drawn in (Makni et al, 2006b) when considering an AR(1) noise model instead of a white Gaussian one in combination with a GMM prior. As the two changes induce higher computation time, it is worth assessing which modelling effort is preferable i.e.…”
Section: Results On Synthetic Datasupporting
confidence: 84%
“…Our method extends previous works (Makni et al, 2005(Makni et al, , 2006b,a) to deal with anatomically informed whole brain analysis. As already done in (Smith et al, 2003;Nieto-Castanon et al, 2003;Flandin et al, 2002), analysis was constrained to the mask of the grey matter obtained from a segmentation of the T1-weighted MRI.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In [8], an autoregressive (AR) noise model has been adopted to account for serial correlations in fMRI time series. It has also been shown in [8] that a spatially-varying AR noise model helped to control false positive rate.…”
Section: Likelihoodmentioning
confidence: 99%